1997
DOI: 10.1016/s0020-7292(97)00154-9
|View full text |Cite
|
Sign up to set email alerts
|

Involving the private sector in improving obstetric care, Anambra State, Nigeria

Abstract: Auxiliaries' skills can be improved with classroom and practical training. The involvement of private sector institutions is important where they provide a substantial proportion of emergency obstetric services. However, maintaining improvements requires sustained efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…Informants in all of the groups were critical of the condescending and hostile attitude of many obstetric nurses. This attitude has been observed elsewhere (Chukudebelu et al 1997;Oyesola et al 1997;Senah et al 1997;Amooti-Kaguna and Nuwaha 2000;). Research conducted prior to the implementation of the Community Health and Family Planning Project in the district in 1994 revealed that all the communities had requested the establishment of clinics (Health on Wheels 2001).…”
Section: Discussionsupporting
confidence: 84%
“…Informants in all of the groups were critical of the condescending and hostile attitude of many obstetric nurses. This attitude has been observed elsewhere (Chukudebelu et al 1997;Oyesola et al 1997;Senah et al 1997;Amooti-Kaguna and Nuwaha 2000;). Research conducted prior to the implementation of the Community Health and Family Planning Project in the district in 1994 revealed that all the communities had requested the establishment of clinics (Health on Wheels 2001).…”
Section: Discussionsupporting
confidence: 84%
“…The private health sector has become increasingly important in the provision of reproductive health services in many middle-and low-income settings (Peters et al, 2004). Demographic and Health Survey (DHS) data have also shown that even the poorest women in poor countries use the for-profit private sector for delivery care (see, for example, Chukudebelu et al, 1997;Hanson & Berman, 1998;Amooti-Kaguna & Nuwaha, 2000). These figures excluded childbirths that took place at home and might have been attended by private sector providers.…”
Section: Introductionmentioning
confidence: 99%
“…A small but significant proportion (between 10 and 15%) of deliveries in many developing countries take place in a private sector facility, with women from wealthy households more likely than women from poor households to deliver their baby at a private sector facility (World Bank, 2002). The availability of private doctors, their responsiveness to patients and women's trust, which is highly valued by both sides, are often given as reasons for many women's preference for the private sector (Chukudebelu et al, 1997;Saénz-Martinez, 1998;Tengilimoglu et al, 1999;Amooti-Kaguna & Nuwaha, 2000;Pongsuppa & Van Lerberghe, 2006). Demographic and Health Survey (DHS) data have also shown that even the poorest women in poor countries use the for-profit private sector for delivery care (see, for example, Chukudebelu et al, 1997;Hanson & Berman, 1998;Amooti-Kaguna & Nuwaha, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Private providers may be sought out by women who cannot or choose not to obtain government services (Brugha and Pritze-Aliassime 2003;WHO 2004). Studies have found that the private sector offers patients flexible payment schedules and greater perceived responsiveness to their needs (Chukudebelu et al 1997;Amooti-Kaguna and Nuwaha 2000). On the supply side, health-care personnel have incentives to work in the private sector, including increased or supplemental salaries (WHO 2004).…”
mentioning
confidence: 99%